HOMONYMS IN BUGIS LANGUAGE: A SEMANTIC STUDY - Rahmat, Subhan (Universitas Muhammadiyah Lampung, 2025)
The study of regional languages holds significant importance as an indicator of cultural identity, a source of communal pride, and a means of preserving the Indonesian language. Among these, the Bugis language, predominantly spoken by communities in several districts of South Sulawesi, serves as a notable example. This paper examines the phenomenon of homonymy in the Bugis language. The primary objective of this research is to analyze the relationships and forms of homonymy present in the language. A qualitative descriptive methodology has been employed, with data collected through oral accounts provided by key informants who are native speakers and possess advanced proficiency in Bugis. The findings indicate that specific terms in the Bugis language exhibit similar semantic properties.